DEVELOPMENT OF SUSTAINABLE ECOTOURISM IN KARANGREJO VILLAGE, KEDIRI USING A BUSINESS MODEL CANVAS WITH INNOVATION STRATEGY AND DIVERSIFICATION OF TOURISM SERVICES - Hakiki, Moh. Saiful; Putra, Riyan Sisiawan; Herlambang, Teguh; Yudianto, Firman; Adinugroho, Mukhtar (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This Community Service activity is a consultation and assistance activity in reviewing the development of business strategics for Sumber Bagindowati Village-Owned Enterprises (BUM Desa) in Karangrejo Village, Kediri Regency, East Java. Sumber Bagindowati is a natural tourism destination that is being renovated to increase tourist attraction. This research combines the principles of Business Model Canvas (BMC), SWOT analysis, and Blue Ocean Strategy (BOS) to design innovative business models. In BMC analysis, elements such as Customer Segments, Value Propositions, Channels, Revenue Streams, Key Resources, Customer Relationships, Key Activities, Key Partnership, and Cost Structure are considered. The results of the SWOT analysis identified strengths, weaknesses, opportunities, and threats affecting BUM Desa Sumber Bagindowati. Business model design using BOS, which involves the question of what can be created, eliminated, improved, and reduced. Innovation is found in strengthening relationships with stakeholders related to network capital, the use of technology such as the use of social media for promotion, the development of multipurpose areas, and new entertainment programs to increase tourist attraction. The business model proposed in this study integrates ideas from BMC, SWOT analysis, and BOS. This business model is expected to help BUM Desa Sumber Bagindowati face competition and increase income, utilize the potential of natural resources, and expand the reach of tourists, including foreign visitors.